The Florida Pinesnake: Pituophis melanoleucus mugitus - Gabriel J. Miller; Steve A. Johnson; Lora L. Smith (EDIS, 2009)
WEC-251, a 6-page illustrated fact sheet by Gabriel J. Miller, Steve A. Johnson, and Lora L. Smith, describes this large, handsome, heavy-bodied snake with dark brown or rust-colored blotches on a light cream to tan background — similar species, distribution and habitats, behavior, diet, reproduction, and conservation. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, February 2009.